Assessing the dynamic changes in vitiligo: reliability and validity of the Vitiligo Disease Activity Score (VDAS) and Vitiligo Disease Improvement Score (VDIS). (29th April 2022) - van Geel, N.; Depaepe, L.; Vandaele, V.; Mertens, L.; Van Causenbroeck, J.; De Schepper, S.; Van Coile, L.; Van Reempts, A.; De Vos, A.‐S.; Papeleu, J.; Hoorens, I.; Mertens, D.; et al.
Abstract: Background: The assessment of the individual evolution of vitiligo is important for therapeutic decision making in daily practice. A fast, simple and validated physician‐reported score to assess clinical changes in depigmentation over time in separate parts (activity and improvement) is currently missing. Objective: The main objective of the study was to develop and validate the Vitiligo Disease Activity Score (VDAS) and Vitiligo Disease Improvement Score (VDIS). Methods: The Vitiligo Disease Activity Score (VDAS) and Vitiligo Disease Improvement Score (VDIS) were evaluated based on a photo set of 66 patients with two different time points. In the first (short) version, only the number of changing body regions was counted based on 15 predefined areas (VDAS15 and VDIS15 ), while in the second (extensive) version the degree of worsening or improvement from +4 to −4 for each body area was added for a more detailed assessment (VDAS60 and VDIS60 ). Content and construct validity were tested. In addition inter‐, intrarater reliability and feasibility were evaluated by 7 (test) and 5 (retest) physicians. Results: Evidence for content and construct validity was provided. Overall, VDAS15, VDIS15, VDAS60 and VDIS60 demonstrated good to excellent inter‐rater reliability [intraclass correlation (ICC): VDAS: range = 0.797–0.900; VDIS: range = 0.726–0.798]. The intrarater reliability ICCs were 0.865 and 0.781 for the VDAS15 and VDIS15, respectively. Similar results were obtained for the VDAS60 and VDIS60 (ICC = 0.913 and 0.800, respectively). Completion time was short (median: 122 s/patient (first round); 95 s/patient (second round)]. Limitations: Single tertiary centre mainly of skin phototype 2 to 3. Conclusion: The VDAS and VDIS appear to be valid, reliable and feasible instruments to score the evolution of vitiligo lesions. This accommodates the current urgent need for a simple, standardized and practical assessment of vitiligo activity and improvement over time.